2019
DOI: 10.3389/fpsyt.2019.00131
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune Diseases and Psychotic Disorders

Abstract: The notion of immunological pathways playing a role in the etiology of a subset of psychotic disorders has received increased interest in the last decades. One of the findings that has spiked interest herein, is an apparent link between autoimmune diseases and psychotic disorders. This is supported by genetic findings associating immune-related genetic markers with schizophrenia and clinical studies finding increased levels of inflammatory markers in patients with psychosis. Several large-scale epidemiologic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
91
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(100 citation statements)
references
References 114 publications
(183 reference statements)
2
91
0
1
Order By: Relevance
“…In this sense, in this study we also found an altered functionality response in B cells, after 3 months of treatment. Altered B cell signaling might also increase the risk of autoimmunity [ 38 ], and as is known, autoimmunity is related to the etiology of schizophrenia [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, in this study we also found an altered functionality response in B cells, after 3 months of treatment. Altered B cell signaling might also increase the risk of autoimmunity [ 38 ], and as is known, autoimmunity is related to the etiology of schizophrenia [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…4a-4c). Altered B cell signaling may also increase the risk of autoimmunity (Rawlings et al, 2017), and as it is known, autoimmunity has been related with the etiology of schizophrenia (Benros et al, 2011;Jeppesen et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Several large scale epidemiologic studies focusing on the relation between autoimmune disease and severe neuropsychiatric illnesses find a role for post-infections autoimmunity through I-Cubed with the production of pathogenic autoantibodies that have targets in brain areas such as the hippocampus, where psychiatric illness develops [7]. The hippocampus is highly dependent upon serotonergic neurotransmission and responsive to selective serotonin and norepinephrine reuptake inhibitors (SSRIs and SNRIs).…”
Section: I-cubed Starts At Sites Of Injury and Inflammation In Responmentioning
confidence: 99%